A CASE STUDY OF TRADITIONAL MANUFACTURING INDUSTRY TRANSFORMATION TO TECHNICAL SERVICES INDUSTRY - Liang-Te Chiang; Chin-Chiuan Lin; Te-Tsai Lu (International Journal of Application on Economics and Business, 2026)
With changing times and rapid technological advancements, the early advantage of cost-driven industries has faded. Former “cash cow industry” are gradually being labeled as traditional industries, or even considered “decline industries.” Traditional manufacturing industry have consistently played a crucial role in Taiwan's economic development, repeatedly contributing to the country's economic miracles. However, in recent years, a growing number of Taiwan's traditional manufacturing company have been investing overseas or undergoing comprehensive transformation. Faced with an increasingly challenging investment environment and rising costs of labor, raw materials, and equipment investment, where should traditional manufacturing industry go from here?. The present study firstly focuses on the transformation of traditional manufacturing industry, exploring the key factors for successful transformation. Secondly, it examines the strategies adopted by companies when facing significant challenges. Through case studies, secondary data collection, and interviews, the present study provides suggestions and references for the transformation strategies of traditional manufacturing industry, based on the results of discussions with actual companies. It also offers questions and directions for future research. The present study identifies the three most important key factors for successful transformation as follows: leadership team, strategic acumen of the leader, and human resource quality.